Accuracy of self‐reported anthropometric measures in older Australian adults. (13th May 2013) - Pasalich, Maria; Lee, Andy H; Burke, Linda; Jancey, Jonine; Howat, Peter
<x xml:space="preserve">Abstract</x> Aim To determine the accuracy of self‐reported anthropometric measurements in older Australian adults 60–70 years. Method Self‐reported anthropometric data from 103 community‐dwelling participants (mean age 66 years) were compared with technician measurements. Difference and agreement were assessed using paired t‐tests, correlation coefficients and Bland–Altman plots. Results Underreporting occurred for weight and hip circumference, especially among men, whereas waist circumference was slightly overreported, resulting in apparent underestimations of body mass index (by 0.42 kg/m2) but overestimations of waist‐to‐hip ratio (WHR, by 0.02). Concordance correlation coefficients were generally high except for WHR. Self‐reported circumference measures appeared to be more accurate than the derived WHR. The Bland–Altman plots revealed wide limits of agreement for all measures. Conclusion Self‐reported values correlated well with technician measured values and average discrepancies were small. However, use of self‐reported anthropometric data may be used more appropriately for describing overall distribution in population studies than for monitoring changes at an individual level.